Student solutions manual to accompany modern macroeconomics - Chugh, Sanjay K. (Cambridge : MIT Press, 2015)
Solutions to odd-numbered problem set questions in Modern Macroeconomics.
Keywords: Macroeconomics -- Problems, exercises, etc; Keynesian economics -- Problems, exercises, etc; Comparative economics -- Problems, exercises, etc